Solvatochromism of Conjugated 4-: N, N -Dimethylaminophenyl-Pyridinium Donor-Acceptor Pairs - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M (Royal Society of Chemistry, 2018)
A series of solvatochromic dyes consisting of an N,N-dimethylaminophenyl donor group conjugated with a 1-butylpyridinium acceptor ring through a 1,4-phenylene spacer were synthesized by a three-step procedure. The procedure involved the synthesis of 4-bromophenylpyrylium salts, their conversion to N-butylpyridinium derivatives, and palladium-catalysed Suzuki-Miyaura coupling reactions. Their UV-vis spectroscopic behaviours, which were investigated in 13 solvents, were compared with the solvatochromism of an amino analogue of Reichardt s ET(30) betaine. All the synthesized dyes showed inverted solvatochromism, which was rationalized by theoretical calculations. © 2018 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.